Associations between the Genetic Polymorphisms of Osteopontin Promoter and Susceptibility to Cancer in Chinese Population: A Meta-Analysis - Liu, Yulan (PLoS One, 2015)
BACKGROUND AND AIM: Several studies have been conducted to examine the associations between osteopontin (OPN) promoter gene SPP1 polymorphisms with human cancers in Chinese population, but the results remain inconsistent. The aim of this meta-analysis is to clarify the associations between SPP1 polymorphisms and cancer susceptibility. METHODS: All eligible case-control studies published up to March 2015 were identified by searching PubMed, Web of Science, Embase, and Cochrane Library without language restrictions. Pooled odds ratio (OR) and 95% confidence interval (95% CI) were calculated using fixed- or random-effect model. RESULTS: A total of 11 case-control studies were included; of those, there were eleven studies (3130 cases and 3828 controls) for -443T>C polymorphism, ten studies (3019 cases and 3615 controls) for -156G>GG polymorphism, eight studies (2258 cases and 2846 controls) for -66T>G polymorphism. Overall, no evidence indicated that the -443 T>C polymorphism was associated with cancer risk (OR = 0.93, 95%CI 0.62–1.38 for dominant model, OR = 1.06, 95%CI 0.73–1.55 for recessive model, OR = 0.88, 95%CI 0.62–1.26 for CT vs TT model, OR = 1.03, 95%CI 0.61–1.73 for CC vs TT model). While, a significantly increase risk was found for -156 G>GG polymorphism (OR = 1.22, 95%CI 1.10–1.35 for dominant model, OR = 1.25, 95%CI 1.10–1.41 for recessive model, OR = 1.18, 95%CI 1.06–1.32 for GGG vs GG model, OR = 1.35, 95%CI 1.09–1.68 for GGGG vs GG model). For -66T>G polymorphism, we found a decrease risk of cancer (OR = 0.84, 95% CI 0.71–0.98 for dominant model), but this result changed (OR = 0.93, 95% CI 0.77–1.12 for dominant model) when we excluded a study. CONCLUSION: This meta-analysis suggests that in Chinese population the -156G>GG polymorphism of SPP1 might be a risk factor for human cancers, while -443T>C mutation is not associated with cancer risk. For -66T>G polymorphism, it may be a protective factor for human cancers.